2018
DOI: 10.32474/ojnbd.2018.01.000108
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Suicidal Ideation among People Living With HIV and Aids Attending Art Clinic at Adult Centre of Excellence University Teaching Hospital, Lusaka

Abstract: Background: Suicidal ideation has long been associated with HIV infected populations worldwide. It has been found that HIV does not only attack the immune system of an individual but also the nervous system leading to psychological dysfunction of an individual. Objective: To establish the prevalence of suicidal ideation among people living with HIV and AIDS. Method: A cross sectional quantitative design was adopted. Systematic random sampling method was used to select the sample. The total sample comprised of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[35] Mwenya et al found that prevalence of suicidal ideation in HIV patients in the ART Clinic Centre in Zambia ( 2018) was 31%, they used suicidal risk screening scale (SRSS) for data collection. [36] Schlebusch et al carried out a study in 190 adult patients in VCT Centre in South Africa (2018), in the 83.1% of the patients who tested HIV-positive the risk of suicidal ideation was 20.5% at 72 hours, while 6 weeks thereafter the risk had increased to 28.8%. They found significant association between suicidal ideation and seropositive HIV status (𝑝 Value = 0.013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[35] Mwenya et al found that prevalence of suicidal ideation in HIV patients in the ART Clinic Centre in Zambia ( 2018) was 31%, they used suicidal risk screening scale (SRSS) for data collection. [36] Schlebusch et al carried out a study in 190 adult patients in VCT Centre in South Africa (2018), in the 83.1% of the patients who tested HIV-positive the risk of suicidal ideation was 20.5% at 72 hours, while 6 weeks thereafter the risk had increased to 28.8%. They found significant association between suicidal ideation and seropositive HIV status (𝑝 Value = 0.013).…”
Section: Literature Reviewmentioning
confidence: 99%